A TOA/AOA Underwater Acoustic Positioning System Based on the Equivalent Sound Speed. (5th June 2018) - Xin, Mingzhen; Yang, Fanlin; Wang, Faxing; Shi, Bo; Zhang, Kai; Liu, Hui
Abstract : High-precision underwater positioning must eliminate the influence of refraction artefacts. Since a Time Of Arrival - Global Navigation Satellite System Intelligent Buoys (TOA-GIB) system does not measure incident beam angles, common refraction correction methods cannot be directly used for refraction artefacts. An Equivalent Sound Speed (ESS) iteration method is proposed and is based on the transformation relations between depth, the ESS gradient and the incident beam angle. On this basis, a TOA/AOA-GIB system without a real-time Sound Speed Profile (SSP) is proposed to estimate the target position and the ESS gradient as unknown parameters. The results from a simulation experiment show that the positioning accuracy of a TOA/AOA-GIB system is better than 0·07% of water depth when the accuracy of the incident beam angle is 0·1 ° .